Multilayer ionic polymer transducer - Akle, Barbar J. (2003)
A transducer consisting of multiple layers of ionic polymer material is developed for applications in sensing, actuation, and control. The transducer consists of two to four individual layers each approximately 200 microns thick. The transducers are connected in parallel to minimize the electric field requirements for actuation. The tradeoff in deflection and force can be controlled by controlling the mechanical constraint at the interface. Packaging the transducer in an outer coating produces a hard constraint between layers and reduces the deflection with a force that increases linearly with the number of layers. This configuration also increases the bandwidth of the transducer. Removing the outer packaging produces an actuator that maintains the deflection of a single layer but has an increased force output. This is obtained by allowing the layers to slide relative to one another during bending. Experiments on transducers with one to three layers are performed and the results are compared to Newbury"s equivalent circuit model, which was modified to accommodate the multilayer polymers. The modification was performed on four different boundary conditions, two electrical the series and the parallel connection, and two mechanical the zero interfacial friction and the zero slip on the interface. Results demonstrate that the largest obstacle to obtaining good performance is water transport between the individual layers. Water crossover produces a near short circuit electrical condition and produces feedthrough between actuation layers and sensing layers. Electrical feedthrough due to water crossover eliminates the ability to produce a transducer that has combined sensing and actuation properties. Eliminating water crossover through good insulation enables the development of a small (5 mm x 30 mm) transducer that has sensing and actuation bandwidth on the order of 100 Hz.